Analysis of the Effects Aquaponic Cultivation Systems on the Growth of Water Spinach (Ipomoea aquatica) and Pak Choy (Brassica rapa L.) - Indriani, Yeni; Ulaan , Magdalin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The degradation of land and water quality in aquaculture has driven the adoption of aquaponics technology as an efficient solution. Aquaponics integrates fish farming and hydroponics, utilizing fish waste as a nutrient source for plants. This study aims to analyze the growth of water spinach (Ipomoea aquatica) and pak choy (Brassica rapa L.), as well as water quality within an aquaponic system using Nile tilapia (Oreochromis niloticus). The research employed a completely randomized design with three treatments: A) aquaponics (fish and plants), B) hydroponics (plants), and C) Nile tilapia pond. The results indicate no significant differences in plant growth regarding height, which ranged from 16.2 cm to 35 cm, and leaf count, which varied from 7.2 to 18.6, between the aquaponics and hydroponics systems. The water quality parameters measured in the aquaponics system included temperature (°C), dissolved oxygen (DO), pH, and concentrations of nitrate (ppm), nitrite (ppm), and ammonia (ppm). All parameters met cultivation standards, except for ammonia levels in treatment C, which registered at 0.25 ppm due to the absence of plants to absorb it. In conclusion, aquaponics effectively supports the growth of both plants and fish while using water more efficiently. Further research is recommended to optimize the combination of fish and plants, along with other environmental factors.